Potencial de regeneração natural em matriz produtiva de eucalipto no bioma Pampa - Granzotto, Fabiane (2022)
The native species natural regeneration in commercial eucalyptus plantations is still poorly studied. Scientific information regarding its potential can contribute with the understanding of ecosystems dynamics associated with the eucalyptus production matrix and assist in decision-making for the conservation and restoration of adjacent natural ecosystems. We investigated the potential of shrub tree species natural regeneration, the expression of soil seed bank (SSB), the ability of this SSB to produce shrub tree seedlings and the relation between regenerating species and environmental variables. We organized the work into four articles and used an area of forest gardens with eucalyptus plantations and native forest remnants in Southeast Serra, Brazilian Pampa, as the study area. In the first article, we analyzed the regenerative potential through the floristic survey of shrub tree species. We confirmed this potential due to the floristic diversity and the expression of rare, endangered and endemic species. We surveyed 13,007 individuals and 113 species in 1.96 ha. The Myrtaceae family and the genus Baccharis are the richest in species, Psychotria leiocarpa Cham. & Schltdl. is the most abundant species in individuals and Podocarpus lambertii Klotzsch ex Endl. occurs in all treatments and regeneration classes. In the second article, we surveyed and characterized the composition of SSB in order to investigate the influence of eucalyptus on natural regeneration. We found that the seed bank quality may be suffering greater influence according to the use and management of treatments in the area according to the native remnants proximity when compared to the presence of eucalyptus. We counted 8,659 seedlings, identified 100 species, 44 families and 88 genera. Asteraceae has the highest species richness and Ichnanthus sp. (Poaceae) is the most abundant species. Trema micrantha (L.) Blume predominates in native areas. In the third article, we evaluated the technique of producing shrub tree seedlings able to use in degraded areas recovery rescued from the SSB. This technique can contribute to increase the diversity of species that have potential use in ecological restoration projects, considering the conditions and place of study. 59.0% of the seedlings survived, distributed in 17 families, 21 genera and 25 species. Trema micrantha is the most abundant species and, at the same time, the one that suffered the greatest loss of individuals (58.3%). In the fourth article, we verified the relation between environmental variables and regenerating shrub tree species. There were two groups formed that, in general, have separated the native remnants from the areas with eucalyptus plantations, reflecting the conservation degree of these environments. Terrain slope, canopy opening, organic matter, calcium, magnesium and aluminum are the most correlated variables to 17 species. Finally, our data suggest that native remnants and Native Forest Edge Eucalyptus patches serve as a buffer in the exotic productive matrix area. Studies of this nature can support the biodiversity management strategies development for areas with eucalyptus plantations under the conditions presented in the study and for Southeast Serra region, Brazilian Pampa.